Analisis Boston Consulting Group (BCG) terhadap Produk Pegadaian: Studi Kasus Pegadaian UPC Ajibarang - Ita Faikotul Mafiroh; Arri Maulida Rakhmawati; Desi Dwi Ruswanti; Yoiz Showa Shafrani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This research explores the strategic positioning of Pegadaian UPC Ajibarang’s products using the Boston Consulting Group (BCG) matrix as a tool for evaluating market performance and future potential. Pegadaian plays a crucial role as a microfinance institution by offering accessible financial solutions such as gold/jewelry pawning, gold savings (digital and physical), installment-based precious metal purchases, electronic pledging, KUR based on vehicle ownership documents, and Hajj savings plans. The study employs a qualitative descriptive approach, gathering insights from comprehensive interviews with both employees and customers. Findings indicate that each product faces unique obstacles and opportunities. Key challenges include customer dissatisfaction regarding service quality, limited adoption of cashless transactions by elderly clients, and traditional promotional methods relying on brochures and word-of-mouth. By mapping products based on market share and growth prospects through the BCG matrix, the study identifies which offerings should be prioritized for development, stability, or rebranding. In response, it is recommended that Pegadaian UPC Ajibarang enhance its marketing and customer service strategies, broaden digital engagement efforts, and introduce user-friendly technological solutions for older clientele. These steps are essential to strengthen competitiveness and ensure long-term sustainable growth for their most promising financial products.